Treatment of metalworking fluids using a submerged anaerobic membrane bioreactor (SAMBR) - Teli, Aronne; Vyrides, Ioannis; Stuckey, David C. (My University, 2015)
BACKGROUND: The role of biodegradation and physical-chemical mechanisms involved in the treatment of metal working fluids (MWFs) using a submerged anaerobic membrane bioreactor (SAMBR) was assessed in this research. Two SAMBRs were employed in series, with the second SAMBR being fed the permeate from the first bioreactor. RESULTS: Results showed a low biodegradability of the MWF both in batch tests (bioconversion efficiency≤3%), and operating the bioreactors continuously (bioconversion efficiency ∼0%). Among the physical-chemical removal mechanisms identified, it was found that bio-adhesion was the most important in MWF removal (removal rate of 96.0±1.64%), whereas membrane rejection was not significant (removal rate of 0.2±0.18%). However, it is expected that membrane separation will play an important role in removal after bio-adhesion has been saturated. CONCLUSION: The inhibition of the hydrolytic/heteroacetogenic biomass was the most problematic aspect in anaerobic digestion, resulting in the need for bioaugmentation of specific microorganisms to degrade MWFs. In the case of non-adaptation during long-term operation, the bio-adhesive propensity of MWFs could be used as a potential method for removing spent MWFs from wastewater streams.
Keywords: Anaerobic digestion; Bioreactors; Industrial effluents; Membranes; Metal working fluids (MWFs); Solid/liquid separation